Hepatic Surgical Stress Promotes Systemic Immunothrombosis That Results in Distant Organ Injury - Zhang, Hongji; Goswami, Julie; Varley, Patrick; van der Windt, Dirk J.; Ren, Jinghua; Loughran, Patricia; Yazdani, Hamza; Neal, Matthew D.; Simmons, Richard L.; Zhang, Jinxiang; Tsung, Allan; Huang, Hai (Frontiers in Immunology, 2020)
Innate immunity can initiate platelet activation during the development of thrombosis through a process, termed immunothrombosis. Neutrophils form neutrophil extracellular traps (NETs) that have been shown to interact directly with platelets and play pro-coagulant roles in a variety of infectious and sterile inflammatory settings. Hepatic surgical stress initiated by ischemia/reperfusion (I/R) injury has wide systemic consequences on distant organs. However, the mechanisms of this remote injury phenomenon are not well understood. Here, we sought to determine the role of NETs in causing systemic immunothrombosis and distant organ injury following a local inflammatory insult with liver I/R. Postoperative thromboelastographic revealed that the speed of clot formation (alpha-angle) was significantly increased whereas time to clot formation (R-time) were decreased by in patients undergoing liver resection, indicating a hypercoagulable state after surgery. In mice subjected to liver I/R, circulating platelet activation and platelet-neutrophil aggregates were significantly increased. Injured distant organs such as the lung and kidney displayed NETs and platelet-rich micro-thrombi in the microvasculature following liver I/R. The immune-thrombi and organ damage were dramatically decreased when NETs were inhibited by DNase treatment. Depletion of Tlr4 on platelets limited NET-induced activation of platelets but had no effect on NET formation. Furthermore, platelet-specific TLR4 KO mice had significantly reduced distant organ injury with decreased circulating platelet activation, platelet-neutrophil aggregates following liver I/R in comparison to their control counterparts. These data establish that after an acute local inflammatory process, NET-activated platelets can lead to a systemic pro-coagulant state with resultant remote organ injury by immunothrombosis.